P3.185 Chlamydia Trachomatis in the Genital Tract of HIV-Infected Women, Pregnant and Non-Pregnant, Followed in a Reference Centre in Bahia, Northeast Brazil. (13th July 2013) - Travassos, A G A; Nóbrega, I; Netto, E; Timbó, M; Adami, K; Fernandes, S; Silva, P; Pires, M; Queiroz, C; Brites, C
Abstract : Background: Genital tract infection by Chlamydia trachomatis (CT) is associated with complications such as pelvic pain, infertility and ectopic pregnancy, besides increased risk of HIV sexual transmission. Its occurrence during gestation worsens perinatal morbidity and mortality. In HIV-infected pregnant women also increases the risk of HIV mother-to-child transmission despite the use of HAART. In Brazil, there are few data on the prevalence of HIV/ CT co-infection and associated risk factors. Methods: Cross-sectional study of HIV-infected women attending in a reference outpatient clinic for gynaecology and prenatal care between October 2010 and September 2011 was conducted, evaluating laboratory and clinical data. The search of CT was performed using Hybrid Capture II collected from endocervix, and clinical data were obtained from standard questionnaire and survey data in medical records. Results: 112 HIV-infected women were enrolled, of whom 52 non-pregnant and 60 pregnant. In this population, mean age was 32.3 years (SD = 8.2), 62.5% had a previous history of sexually transmitted diseases, 46.4% began sex life with 15 years or less, 33.1% reported having less than 3 sexual partners throughout life, 45.8% had undetectable HIV viral load. We found a prevalence of 5.4% of Chlamydia trachomatis infection in HIV-infected women followed. There was an association of CT with the presence of pregnancy (10.0% versus 0.0%; p = 0.019), HIV viral load > 10, 000 copies (p < 0.001) and the mean time of HIV diagnosis (21.0 versus 69.2 months; p = 0.032). We found no association with other risk factors studied (ethnicity, marital status, education, use of alcohol and drugs, CD4 + T Lymphocyte count). Conclusion: Early access to diagnosis and treatment of infection by HIV and Chlamydia trachomatis is an important preventive action. In pregnant women infected with HIV, the prevalence of Chlamydia appears to be greater and this is a period where treatment can improve maternal and neonatal outcome.